The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.pedhc.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Health Insurance and a Usual Source of Care on a Child’s Receipt of Health Care

Abstract: Introduction Recent health reforms will expand US children’s insurance coverage. Yet, disparities persist in access to pediatric care, even among the insured. We investigated the separate and combined effects of having health insurance and a usual source of care (USC) on children’s receipt of health care services. Methods We conducted secondary analysis of the nationally-representative 2002-2007 Medical Expenditure Panel Survey data from children (aged ≤18 years) who had at least one health care visit and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…SES indicators) for this analysis were maternal educational attainment, annual household income, and insurance type. For this study, education was considered a stable measure of SES (17), income was indicative of current access to resources (5, 18), and insurance status was a marker of access to healthcare services (6). We derived a composite socioeconomic index (SES index)(15, 1921) for each participant by summing the ordinal rank scores as follows: Maternal educational level was categorized into low (less than high school graduate, score=1), medium (high school graduate, score=2), and high (some college or higher, score=3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SES indicators) for this analysis were maternal educational attainment, annual household income, and insurance type. For this study, education was considered a stable measure of SES (17), income was indicative of current access to resources (5, 18), and insurance status was a marker of access to healthcare services (6). We derived a composite socioeconomic index (SES index)(15, 1921) for each participant by summing the ordinal rank scores as follows: Maternal educational level was categorized into low (less than high school graduate, score=1), medium (high school graduate, score=2), and high (some college or higher, score=3).…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancy in asthma outcomes is multifactorial and greatly influenced by social adversities, such as poverty, that disproportionately affect African American populations (3). Socioeconomic status (SES) is often measured by educational level, annual household income, and insurance status (46). Individuals with low educational attainment are at high risk for poor health literacy (7), and low parental literacy is associated with moderate and severe persistent asthma as well as higher rescue medication use in children (8).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Furthermore, access to patient-centered, comprehensive primary care has been shown to improve delivery of preventive services and decrease unmet medical needs of children. 5,6 Pediatricians and family physicians make up the majority of the current physician workforce responsible for providing primary care for children. While pediatricians account for a large proportion of physician visits by children, family physicians are named as the usual source of care for one-third of the child population and provide 16% to 21% of physician visits by children.…”
Section: Introductionmentioning
confidence: 99%
“…39 We have also shown that adults and children are both more likely to have unmet health care needs when they lack a USC, even if they have health insurance. 40,41 In this study, we report on the importance of a USC for both parent and child, even while controlling for parental and child health insurance. …”
mentioning
confidence: 98%